The Therapeutic Effect of Traditional LiuJunZi Decoction on Ovalbumin-Induced Asthma in Balb/C Mice - Wenting Xu; Rui Zhao; Bin Yuan (Canadian Respiratory Journal)
Aim. To investigate the therapeutic effect of LiuJunZi decoction (LJZD) in an experimental model of asthma and uncover its potential mechanism. Materials and Methods. The ovalbumin (OVA) was applied to induce asthma in Balb/C mice, and LJZD was orally administrated to asthmatic mice. The lung function and histological lesion were evaluated by airway hyperresponsiveness assay, lung edema assay, and hematoxylin and eosin staining. The amounts of CD4+CD25+Foxp3+ TReg cells were analyzed through combining fluorescent antibody staining with flow cytometry assay. The levels of inflammatory factors and immunoglobulins were detected by enzyme-linked immuno sorbent assay (ELISA). The expression of miR-21 and miR-146a was investigated by real-time PCR. The protein expression of activating protein-1 (AP-1), nuclear factor kappa-B (NF-κB), and NF-κB inhibitor alpha (IκBα) was determined by western blotting. Results. LJZD improves OVA-induced asthma in Balb/C mice, which is manifested by decreasing lung edema, Penh levels, lung histological lesion, and inflammatory cell infiltration. LJZD increased the number of CD4+CD25+Foxp3+ TReg cells in blood mononuclear cells from asthmatic mice. Furthermore, LJZD reduced the levels of tumor necrosis factor-α (TNF-α), interleukin- (IL-) 4, IL-6, IgG1, and IgE, but increased interferon gamma (IFN-γ) expression, in serum of asthmatic mice, and also decreased the expression of IL-17a, IL-23, IL-25, and thymic stromal lymphopoietin (Tslp) in lung tissues. In addition, miR-21 and miR-146a expression and phospho (p)-NF-κB, p-IκBα, and AP-1 protein expression were inhibited by LJZD in lung tissues from asthmatic mice. Conclusion. LJZD improved OVA-induced asthma in Balb/C mice by inhibiting allergic inflammation and Th2 immunoreaction, which might be associated with the inactivation of the NF-κB signaling pathway.